The state of the cytokine profile in pregnant women with non-alcoholic fatty liver disease at the stage of non-alcoholic steatohepatitis with varying degrees of comorbid obesity under the influence of the developed complex therapy program - L. V. Bahnii; S. M. Heriak; N. I. Bahnii (Zaporožskij Medicinskij Žurnal)
The aim of the study: to evaluate the cytokine profile state in pregnant women with non-alcoholic fatty liver disease (NAFLD) at the stage of non-alcoholic steatohepatitis (NASH) with varying degrees of obesity under the influence of the developed complex therapy program.